2021
DOI: 10.3390/catal11030307
|View full text |Cite
|
Sign up to set email alerts
|

ω-Transaminase-Mediated Asymmetric Synthesis of (S)-1-(4-Trifluoromethylphenyl)Ethylamine

Abstract: The pivotal role played by ω-transaminases (ω-TAs) in the synthesis of chiral amines used as building blocks for drugs and pharmaceuticals is widely recognized. However, chiral bulky amines are challenging to produce. Herein, a ω-TA (TR8) from a marine bacterium was used to synthesize a fluorine chiral amine from a bulky ketone. An analysis of the reaction conditions for process development showed that isopropylamine concentrations above 75 mM had an inhibitory effect on the enzyme. Five different organic solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The highest conversion was achieved with DMSO, with only 1% of reduction in conversion being observed when compared with the control reaction without cosolvent added. In a previous study with a marine ω-transaminase, we also observed that DMSO was the cosolvent allowing the highest retention of activity [ 52 ]. DMSO is often mentioned as a cosolvent in the literature due to improved substrate solubility and enzyme properties, although it may difficult to extract the components from the aqueous phase and wastewater treatment [ 51 ].…”
Section: Resultsmentioning
confidence: 96%
“…The highest conversion was achieved with DMSO, with only 1% of reduction in conversion being observed when compared with the control reaction without cosolvent added. In a previous study with a marine ω-transaminase, we also observed that DMSO was the cosolvent allowing the highest retention of activity [ 52 ]. DMSO is often mentioned as a cosolvent in the literature due to improved substrate solubility and enzyme properties, although it may difficult to extract the components from the aqueous phase and wastewater treatment [ 51 ].…”
Section: Resultsmentioning
confidence: 96%
“… 31,50,51 Some strategies, including screening organic solvents and adding co-solvents such as DMSO and acetone to the enzymatic-catalysis synthesis system with two aqueous-organic phases, can increase the concentration of insoluble substrates, and thereby increase the reaction rate. 52–55 …”
Section: Discussionmentioning
confidence: 99%
“…In another study carried out by us, an ω-transaminase from a marine bacterium was investigated for bioconversion of bulky ketones to chiral amines [ 142 ]. The bioprocess development allowed the fast assessment of suitable reaction conditions.…”
Section: Bioprocess Developmentmentioning
confidence: 99%